The Effectiveness Of Computer-Assisted Instruction In Learning Science - Ong, Eng Choon (1999)
Computer-Assisted Instruction (CAI) has become increasingly popular nowadays. As mentioned by many well-known CAI researchers, the CAI method uses mainly Interactive Multimedia Instruction (IMI) program via computers to impart knowledge to the students. Many programs and learning materials from Internet or those available on CD-ROMs are IMI materials. How effective is CAI as a learning tool? It is the main focus of this study. This study also investigated whether the factor of gender and students’ prior knowledge of computers influenced achievement and finally students’ perception towards CAI. The study was conducted on a Form Two Science topic using CDROM program. It involved 73 students from a secondary school in Temerloh, Pahang. The subjects learnt using CAI method via computer, replacing the existing traditional textbook method. Before the CAI sessions, students took a pretest, They also answered a questionnaire on students’ perception towards CAI. After the CAI treatment, all the subjects sat for a post-test to assess the academic achievement. The students answered the questionnaire again to assess changes in perception towards CAI. The results showed that CAI method significantly improved students’ academic achievement. This study revealed that CAI method was effective in learning Science for the secondary school students. The results indicated that the effectiveness of learning through CAI was not affected by gender. There was also no significant difference in the perception of computers as a learning tool between boys and girls. There were significant results showed that there was an increase in students’ perception towards the use of computers. The results also revealed that the students’ prior knowledge of computers did not affect the achievement in CAI. The findings suggest that future researches should focus on a longer duration of CAI sessions in order to obtain more reliable results. The present CAI sessions were only limited to 3 weeks. The implication of the study was that parents should make available PCs for their children, and likewise the Ministry of Education should equip schools with more PCs. This is because of the positive perception towards computers and CAI. However, it is recommended that more studies be conducted to assess the effectiveness of CAI on achievement in other academic subjects.